Using the Ball-in-Bowl Metaphor to Outline an Integrative Framework for Understanding Dysregulated Emotion - Nowak, Ulrike; Wittkamp, Martin F.; Clamor, Annika; Lincoln, Tania M. (Frontiers in Psychiatry, 2021)
Dysregulated emotion plays an important role for mental health problems and different strands of research have focussed on elucidating its underlying mechanisms. The domains that research has focused on so far include strategy-based emotion regulation, psychophysiological self-regulation, emotion evaluations, and resulting emotion dynamics. These domains have been looked at in relative isolation from each other and mutual influences and combined effects are seldom considered. Here, we summarise the most influential domain-specific models of dysregulated emotion, the research questions they have stimulated as well as their strengths and weaknesses for research and clinical practice. We argue that the domain-specific focus constrains the progress the field is able to make. We then introduce a metaphor of a ball in a bowl to outline an integrative framework of strategy-based emotion regulation, psychophysiological self regulation, emotion evaluations, and resulting emotion dynamics. We illustrate how such a framework can inspire new research on the interactions between different domains of dysregulated emotion, how it can help to explain a broader array of findings, and how it can facilitate the tailoring of interventions to patients’ specific regulatory impairments.